Human Papilloma Virus Vaccine for Cervical Cancer Prevention - Sultana, Chowdhury Shamima (Journal of Bangladesh College of Physicians and Surgeons, 2021)
HPV infection is estimated to be responsible for about 5% of human cancers worldwide. Among all HPV-associated malignancies, cervical cancer is the most important cause of morbidity and mortality worldwide. Cervical cancer is the fourth most common cancer in women worldwide and leading cause of cancer death among females in less developed countries. Persistent HPV infection is a necessary cause of invasive cervical cancer with a prevalence of 99.7% in cervical cancer worldwide.At least 70% of cervical cancers are caused by HPV 16 and HPV 18. HPV vaccination in combination with regular screening offers the most effective way for women to be protected against cervical cancer.The global burden of cervical cancer falls heaviest on the developing countries which haven’t introduced the HPV vaccine as part of their national public health strategy to prevent and control cervical cancer. Different studies showed a drop in the prevalence of HPV associated diseases in vaccinated populations. Sustained efficacy, immunogenicity, and safety of the bHPV vaccine were observed in the final analysis of a follow-up study up to 9.4 years postvaccination. Cervical cancer is a major public health problem in Bangladesh. There has been little success with screening program against cervical cancer in Bangladesh. Therefore, a National HPV Vaccination Program seems to be the window of opportunity to reduce the mortality and morbidity of cervical cancer in Bangladesh. J Bangladesh Coll Phys Surg 2021; 39(2): 123-131